2013
DOI: 10.1210/jc.2013-1645
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Hearing Impairment in Patients With Congenital Hypothyroidism Treated Since the Neonatal Period: A National Population-Based Study

Abstract: Despite major improvements in prognosis, hearing loss remains a significant problem, particularly in patients with severe CH. Parents and primary care providers should be aware of this risk, because early diagnosis and intervention could improve the long-term prognosis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 39 publications
2
43
1
4
Order By: Relevance
“…One study investigated 12 older patients, at the age of 20 years, and suggested that auditory processing abnormalities persisted in these patients (59). In our nationwide study of 1202 young adult patients, we have recently shown that, at a median age of 23.4 years, a significantly larger proportion of the CH population than of the general population reported having hearing impairment (9.5 vs 2.5%) and that the risk of developing hearing impairment was more than three times higher in these patients than in the reference population (29,60). Hearing loss was mostly detected during childhood, at a median (23-75th percentile) age of 7.0 (3.4-19.0) years and 17% of the patients who declared hearing impairment at a median age of 23.4 years had required a hearing aid since a median age of 10 years.…”
Section: Neurosensory Developmentmentioning
confidence: 84%
“…One study investigated 12 older patients, at the age of 20 years, and suggested that auditory processing abnormalities persisted in these patients (59). In our nationwide study of 1202 young adult patients, we have recently shown that, at a median age of 23.4 years, a significantly larger proportion of the CH population than of the general population reported having hearing impairment (9.5 vs 2.5%) and that the risk of developing hearing impairment was more than three times higher in these patients than in the reference population (29,60). Hearing loss was mostly detected during childhood, at a median (23-75th percentile) age of 7.0 (3.4-19.0) years and 17% of the patients who declared hearing impairment at a median age of 23.4 years had required a hearing aid since a median age of 10 years.…”
Section: Neurosensory Developmentmentioning
confidence: 84%
“…Thus, several audiological findings are possible. However, the audiometric disturbances are frequently described as having the following features: sensorineural, bilateral, symmetric, mainly in high frequencies, in a varying degree, and are often mild to moderate severity (6,7,(41)(42)(43)(44)(45)(46). Conductive hearing loss and tympanometric abnormalities in addition to acoustic middle ear reflex have also been described in several studies (5,6,7,(41)(42)(43).…”
Section: Retrocochlear/central Mechanisms On Congenital Hypothyroidismmentioning
confidence: 99%
“…No entanto, a exata prevalência da perda auditiva nos portadores de HC permanece em discussão. Estima-se que o risco de desenvolver perda auditiva nessa população seja de duas a quatro vezes maior que na população geral de crianças para a mesma faixa etária 25 , podendo afetar cerca de 20% dos portadores de HC 4 . É importante destacar que a frequência de hipoacusia encontrada no presente estudo não reflete necessariamente a presença de perda auditiva, com redução nos limiares tonais.…”
Section: Os Indivíduos Apresentamunclassified